Two species of the genus Euconnus Thomson (Coleoptera: Staphylinidae: Scydmaeninae) new to Korea - Ui-Joung Byeon; Min-Ho Song; Jong-Seok Park (Journal of Asia-Pacific Biodiversity, 2023)
The genus Euconnus Thomson (Coleoptera: Staphylinidae: Scydmaeninae) includes four species in Korea. In this study, E. (s. str.) fustiger and E. (s. str.) dulcis are recorded for the first time Korea and E. (Cladoconnus) rudimentalis is redescribed. As a result, the number of the Korean species of Euconnus is increased to six. A key descriptions, habitus illustrations, diagnostic characters, and a distribution map are provided.